2022
DOI: 10.3390/cancers14215373
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin, a Potent Anticancer Compound: From Chemistry to Cellular Interactions and Synergetic Perspectives

Abstract: Increasing rates of cancer incidence and the toxicity concerns of existing chemotherapeutic agents have intensified the research to explore more alternative routes to combat tumor. Luteolin, a flavone found in numerous fruits, vegetables, and herbs, has exhibited a number of biological activities, such as anticancer and anti-inflammatory. Luteolin inhibits tumor growth by targeting cellular processes such as apoptosis, cell-cycle progression, angiogenesis and migration. Mechanistically, luteolin causes cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 153 publications
0
17
0
Order By: Relevance
“…The anticancer properties of Luteolin have been related to its ability to inhibit proliferation, metastasis, and invasion of tumor cells and angiogenesis by various mechanisms, including the suppression of kinases, promotion of apoptosis, regulation of the tumor cell cycle, and reduction in transcription factors ( Figure 2 ) [ 17 ]. The induction of apoptosis has been linked with Luteolin’s anticancer properties, which involve DNA damage, regulation of redox, and protein kinases in inhibiting cancer cell proliferation ( Figure 3 ) [ 39 ].…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer properties of Luteolin have been related to its ability to inhibit proliferation, metastasis, and invasion of tumor cells and angiogenesis by various mechanisms, including the suppression of kinases, promotion of apoptosis, regulation of the tumor cell cycle, and reduction in transcription factors ( Figure 2 ) [ 17 ]. The induction of apoptosis has been linked with Luteolin’s anticancer properties, which involve DNA damage, regulation of redox, and protein kinases in inhibiting cancer cell proliferation ( Figure 3 ) [ 39 ].…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
“…For years, plants have been used as complementary therapies or dietary agents to manipulate cellular signaling. In light of this, many recent studies showed that among the plant-based compounds, Luteolin could suppress the process of carcinogenesis by altering different cellular events in cancer cells, promoting apoptosis; inducing cell cycle arrest; thus causing perturbation in cell cycle progression; and inhibiting proliferation, migration, and invasion of cancer cells [ 17 ]. The anticancer properties of Luteolin have been demonstrated in various cancer types in preclinical settings, and these anticancer effects were found to be regulated through its interaction with different molecular target sites and regulation of several signaling pathways in cancer cells [ 8 , 18 ]; however, no clinical studies of Luteolin have been conducted for cancer treatment yet [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has a golden crystalline form and a C 6 –C 3 –C 6 carbon skeleton with two benzene rings connected by a heterocyclic ring. [ 17 ] Polyphenols and flavonoids protect plant cells from UV radiation, bugs, and other pests. Investigations on cultured cells, livestock populations, and human beings have shown proof that flavonoids are advantageous to the health of humans and animals.…”
Section: Luteolin and Its Immunomodulatory Effectsmentioning
confidence: 99%
“…It has a golden crystalline form and a C 6 -C 3 -C 6 carbon skeleton with two benzene rings connected by a heterocyclic ring. [17] Polyphenols and flavonoids protect plant cells from UV radiation, bugs, and other pests.…”
Section: Luteolin and Its Immunomodulatory Effectsmentioning
confidence: 99%
“…These natural flavones are considered a strong starting point for the development of anticancer agents, as they can alleviate inflammation, inhibit the proliferation, migration, and invasion of cancer cells, and induce malignant cell death through mechanisms such as apoptosis and autophagy. For instance, when administered with conventional chemotherapy, luteolin has been proven to enhance anticancer effects. …”
Section: Introductionmentioning
confidence: 99%